The effect of maternal diabetes on the formation of fetal surfactant - Sanjaya, I Nyoman Hariyasa; Sutandi, Chatrine (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2024)
Elevated maternal blood glucose levels in pregnancy correlate with increased risk of pregnancy complications, labor, and pregnancy outcomes. Type II alveolus cells produce a combination of fat and protein called pulmonary surfactant. To assist in preserving lung stability, pulmonary surfactant plays a crucial function in lowering the propensity of the alveolus to recoil and preventing alveolus collapse. The hallmark of maternal diabetes is the malfunctioning of pancreatic β-cells, which results in insufficient insulin production to sustain proper blood glucose levels. Respiratory distress syndrome (RDS) in newborns is caused by surfactant lack of sufficiency, which is caused by fetal hyperglycemia and hyperinsulinism brought on by maternal diabetes. Appropriate treatments are required to improve glycemic management since maternal diabetes raises the risk of RDS in term newborns. These therapies include a deeper comprehension of the molecular mechanisms behind gestational diabetes mellitus that impact the surfactant system. Phosphatidylglycerol levels are either nonexistent or extremely low in infants with RDS. Phosphatidylglycerol synthesis during pregnancy in diabetics is known to be delayed in comparison to the non-diabetic control group. For this reason, proper care is essential to enhancing long-term health and neonatal outcomes. These findings underscore the need for early detection and management of maternal diabetes to mitigate the risk of RDS and improve neonatal health.